Krleža’s polemical strategies and Danilo Kiš’s "The Anatomy Lesson" - Krcić, Nenad (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
This paper examines D. Kiš’s imitation of polemical strategies used by M. Krleža in the polemical book The Anatomy Lesson. Analyzing Krleža’s polemical style, K. Bagić (1999) mentions the quotability and the process of dramatizing quotes (the so-called rhetoric of quotes), and points out that many inherited this process from Krleža, but that he particularly embraced and developed it (to the point of his polemical strategy). Krleža’s great admirer, D. Kiš, in the aforementioned polemical book. Free indirect speech, dramatization of quotations and generalization of conflicts using polemical maxims for Bagić are the mainstays of Krleža’s polemical style (his polemical strategy), and similar strategies are also recognized in The Anatomy Lesson. Apart from that, quantification also stands out as a feature of Krleža’s polemical style, and it is one of the key features of Kiš’s polemical style, so it could be concluded that Kiš really looked up to Krleža when writing this book.